Dampak Jangka Panjang Bullying di Masa Sekolah Dasar terhadap Kesehatan Mental Anak - Zuhriyah, Aminata; Damayanti, Dina; Safitri, Wulan Erliana; Darsono, Darsono (Jurnal Bimbingan dan Konseling Pandohop, 2025)
Bullying in elementary schools is a concerning issue with long-term consequences for children's mental health. This study aims to comprehensively examine various forms of bullying and their psychological impacts on victims from childhood through adulthood. Using a literature review method, data were collected from relevant scientific sources published within the last ten years. The findings reveal that children who experience bullying in elementary school are at significantly higher risk of developing depression, anxiety disorders, PTSD, low self-esteem, eating disorders, and suicidal tendencies. These effects also influence academic achievement, social development, and overall long-term well-being. The results highlight the urgent need for early interventions, active engagement of educational stakeholders, and multisectoral approaches to bullying prevention. This study contributes to the academic understanding of the importance of protecting children's mental health from an early age through structured anti-bullying policies and programs.